Dynamic behaviour of fibre-reinforced recycled aggregate concrete beams under low-velocity impact load - Htet, P.; Chen, Wensu; Huang, Z.; Pham, T.M.; Tran, D.T.; Hao, Hong (2025)
Despite increasing interest in recycled aggregate concrete (RAC), most structural-level studies have focused on the performance of RAC beams under static loads, with limited studies assessing their dynamic performance. No studies have been reported on the impact response of RAC or fibre-reinforced recycled aggregate concrete (FRRAC) beams with fibre-reinforced polymer (FRP) reinforcement. In this study, seven beams (one made of natural aggregate concrete as the control, three RAC and three FRRAC) reinforced with steel bars, basalt FRP (BFRP) bars or steel-basalt FRP composite bars (SBCBs) were prepared and subjected to multiple impacts using a pendulum impact system. The influences of aggregate type, reinforcement type, and fibre addition (macro-basalt and recycled macro-polypropylene fibres at 1.34 % by volume dosage) were assessed by comparing the failure mode, impact force, reaction force, deflection and reinforcement strain. Compared to steel-reinforced RAC beams, beams reinforced with BFRP bars and SBCBs experienced higher peak impact forces, lower residual deflections, and withstanding higher impact velocity (up to the 3rd impact) without failure. The hybrid fibre addition to RAC beams led to higher peak impact forces and reduced the maximum and residual deflections. In addition, spalling damage and concrete crushing failure modes were effectively mitigated.